Acetate promotes lipogenesis in adipocytes but not in hepatocytes of chickens. Issue 1 (2nd January 2022) - Liu, S.; Zhao, L.; Xiao, X.; Jiang, W.; Ju, Z.; Tian, M.; Li, H.; Lin, H.
ABSTRACT: 1.The role of acetate in lipogenesis of chickens remains largely unknown. This trial investigated the effect of sodium acetate (SA) on chicken fat metabolism via in vivo and in vitro experiments. 2.The results indicated that supplementation of SA (1.0 g/kg feed) showed marginal to moderate stimulation on the area of the abdominal fat cells and triglyceride (TG) content in liver and adipose tissues. It increased the transcription of some genes involved in fat synthesis and deposition, but did not affect free fatty acid receptor 2 ( FFAR2 ) expression in either liver or abdominal fat. 3. In cultured hepatocytes treated with 0.01 mM to 5 mM SA, although mRNA levels of ACC1, PPAR, SREBP-1 c, and FFAR2 were upregulated with SA at certain concentrations, TG content and protein expression of lipogenic genes and FFAR2 were not altered at any dosages. In adipogenic differentiation of preadipocytes, high concentrations of SA (5 mM) exhibited significant increments in TG content and accumulated fat droplets, associated with stimulated transcription of FAS, LPL, AD, FABP4, and FFAR2, as well as elevated protein expression of FABP4 and FFAR2. 4. The results showed that adipocytes were more sensitive to acetate than hepatocytes in chickens. While acetate played a minor role in hepatic fat metabolism, it promoted lipogenesis in adipocytes via FFAR2 with the involvement of FAS, LPL, and FABP4.